Misunderstanding Jamaluddin Afghani by Muslims of South Asia: the Radical Interpretation - Balkhi, Mirwais (CenRaPS Journal of Social Sciences, 2022)
Sayyid Jamaluddin Afghani is one of the great features of Islamic reformism, Pan Islamism, and anti-colonialism in the nineteenth century who with the great and revolutionary thoughts has overshadowed all the intellectual and political groups in the Muslim world. This revivalist of the time with numerous trips to distant lands and nearly everywhere sought to awaken Muslims and the Eastern nations to eradicate roots of the Western colonial powers. Indian sub-continent was the primary goal for Jamaluddin Afghani. In his first trip to the sub-continent and the major cities of British India, he tirelessly sought to awaken the Muslim population in that country. He had also dealings with Indian people at the time when he was living outside the sub-continent. Jamaluddin had awakened the generations of his own time and the next. Allama Muhammad Iqbal, Ubaidullah Sindhi, Maulana Abul Kalam Azad, Abul A’la Maududi, respectively, the prominent figures of pan Islamism, radical Islam, and Islamic modernity, in South Asia are impressed by Afghani’s thoughts. But the above-mentioned generations failed to transfer his original ideas of to the present Muslim generation of the Indian sub-continent. This paper attempts to discuss the relationship of Jamaluddin Afghani with the Indian sub-continent and the influence of his thought on the generations from the past to the present.